FLUKTUASI DAN KOMPOSISI KOMUNUAS FITOPLANKTON DI PERAIRAN MANGROVE P. DUA (TELUK BANTEN) 1985 - 1986 - MULYADI, MULYADI (BERITA BIOLOGI, 1989)
MULYADI. 1989. Fluctuation and composition of phytoplankton community on Dua island mangrove waters (Ban ten bay) 1985 - 1986. Berita Biologi 3(9): 445 - 449.The study was carried out form July 1985 to June 1986 and a number of 29 phytoplankton genera were recorded.Spatial distribution of each genus within the mangrove waters due to the difference of habitat tolerance.Skeletonema, Thalassiosira and Nitzschia are the genera which have wide distribution (22.5%, 17.2% and 15.2% of distribution percentage respectively).The distributions of those genera are not always followed by high abundance. The number and abundance of phytoplankton were higher during the dry season than the rainy season.The highest density of phytoplankton community was recorded in July while the lowest was in March..